The Concept of WARRIOR in the Linguistic World View of Ukraine and Spain in the 21st Century - Сморокова, Еліна (Київський національний університет імені Тараса Шевченка, 2023)
The article provides an in-depth examination of the evolving concept of “warrior” during Russian aggression in Ukraine. It highlights the paramount importance of cognitive linguistics in unravelling the ways in which language shapes and is shaped by our beliefs, particularly in times of social and political unrest. Based on an analysis of Ukrainian and Spanish media, this study highlights the significant impact of cultural and cognitive frameworks on the communication of concepts in language. This understanding provides an essential basis for a comprehensive study of the development of the concept in different cultural and linguistic contexts. The research definitively establishes the importance of cultural influences in shaping linguistic expressions and, consequently, worldviews and ideologies. It also reinforces the idea that language is not just a means of communication, but a powerful tool for propaganda, persuasion, and the construction of national identities. The use of Ukrainian and Spanish media as analytical focal points allows for a cross-cultural and cross-linguistic comparison, enhancing our understanding of how the notion of a 'warrior' is perceived and represented in these unique contexts. The article offers an insightful perspective that sheds light on the complex interplay between language, culture and evolving social dynamics.

Статтю присвячено дослідженню ціннісного та асоціативного аспектів концепту ВОЇН, який набув нових конотацій на тлі російської агресії на території України. Засоби масової інформації підкреслюють важливість когнітивної лінгвістики для виявлення того, як мова віддзеркалює і впливає на наше сприйняття, особливо в періоди соціальних і політичних заворушень. Проаналізувавши українські та іспанські ЗМІ, ми дійшли висновку, що культурні та ментальні рамки глибоко вкорінюють концепти в мові. Таке розуміння закладає необхідне підґрунтя для всебічного аналізу еволюції концепту “воїн” у різних культурних та мовних контекстах. Встановлено значення культурних впливів у формуванні мовних виразів, а отже, світогляду і думок. Дослідження підтверджує уявлення про мову як, у тому числі, про інструмент пропаганди, переконання та формування національної ідентичності. Вибір української та іспанської медіа дозволив провести аналіз у двох лінгвокультурних контекстах.
Концепт ВОЇН у мовній картині світу України й Іспанії XXI століття
Keywords: концепт; аспект; метафора; публіцистичний дискурс; війна; політичний дискурс; преса; concept; aspect; metaphor; journalistic discourse; war; political discourse; press